Assessment of Do Son Beach Changes using Monitoring Camera Images - Cong Huu, Vu; Van Uu, Dinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 4, 2021)
In recent years, camera technology has been used in the field of beach variation and beach protection. This study presents the results of processing images of Do Son beach based on images. Camera image processing is calibrated based on real measurements of control points. Camera images are processed to capture shoreline and beach developments for the period from August 2018 to October 2019. The results show that Do Son beach has short term and seasonal fluctuations. Beach geomorphology tends to reach equilibrium form.